2005
DOI: 10.1111/j.1365-2141.2005.05851.x
|View full text |Cite
|
Sign up to set email alerts
|

PRIMA‐1 induces apoptosis in acute myeloid leukaemia cells with p53 gene deletion

Abstract: Summary The p53 tumour suppressor gene located on chromosome 17p13 is the most frequently mutated gene in human tumours. About 5–8% of cases with acute myeloid leukaemia (AML) carry the p53 mutation. Recently, the compound p53‐dependent reactivation and induction of massive apoptosis (PRIMA‐1) has been shown to induce cytotoxic effects and apoptosis in human tumour cells by restoration of the transcriptional activity of mutated p53. This is believed to be mediated by a change in the conformation of mutated p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 33 publications
3
44
0
1
Order By: Relevance
“…The enzyme ATM phosphorylates p53, creating a stabilized molecule with enhanced transcriptional activity (Banin et al, 1998), (Lambert et al, 1998). Notably, samples with ATM deletion were more sensitive to RITA than TP53-deleted samples, a result in line with an earlier observation that RITA has a direct effect on p53 without a need for its phosphorylation (Issaeva et al, 2004).In a previous study, we showed that PRIMA-1 was more toxic to both AML and CLL cells with mutated TP53 compared with cells with wt p53 (Nahi et al, 2004(Nahi et al, , 2006. In the present study, this was confirmed in AML, with PRIMA-1 having a fivefold lower IC50 in samples with )17.…”
supporting
confidence: 83%
“…The enzyme ATM phosphorylates p53, creating a stabilized molecule with enhanced transcriptional activity (Banin et al, 1998), (Lambert et al, 1998). Notably, samples with ATM deletion were more sensitive to RITA than TP53-deleted samples, a result in line with an earlier observation that RITA has a direct effect on p53 without a need for its phosphorylation (Issaeva et al, 2004).In a previous study, we showed that PRIMA-1 was more toxic to both AML and CLL cells with mutated TP53 compared with cells with wt p53 (Nahi et al, 2004(Nahi et al, , 2006. In the present study, this was confirmed in AML, with PRIMA-1 having a fivefold lower IC50 in samples with )17.…”
supporting
confidence: 83%
“…Our further studies of PRIMA-1 and its structural analog PRIMA-1 MET (APR-246) showed that these compounds inhibit human xenograft tumor growth in SCID mice (Bykov et al, , 2005b and growth of mouse tumors in a syngeneic host (Zache et al, 2008b). They also show potent effect on primary human acute myeloid leukemia and chronic lymphoid leukemia cells (Nahi et al, 2004(Nahi et al, , 2006. Furthermore, we showed that PRIMA-1 MET (APR-246) is able to synergize with certain chemotherapeutic drugs, including adriamycin and cisplatin (Bykov et al, 2005b).…”
Section: Screening For Mutant P53-reactivating Compoundsmentioning
confidence: 86%
“…In this regard, interesting results about the substance PRIMA-1 (p53-dependent reactivation and induction of massive apoptosis) were published recently. 39 Furthermore, the latest results of research showed improvement in the in vitro drug chemosensitivity in p53-deleted cells after coincubation of RITA (reactivation of p53 and induction of tumor cell apoptosis) and PRIMA-1. 40 …”
Section: Discussionmentioning
confidence: 99%